Sonic the Hedgehog - Fowler, Jeff 1978-; Casey, Patrick 1978-; Miller, Josh; Moritz, Neal H.; Ascher, Toby 1983-; Nakahara, Toru (Producer); Ito, Takeshi (Film producer); Marsden, James 1973-; Schwartz, Ben 1981-; Sumpter, Tika; Rothwell, Natasha 1980-; Pally, Adam 1982-; et al. (Hollywood, California Paramount Pictures, 2020)
After discovering a small, blue, fast hedgehog, a small-town sheriff must help him defeat Dr. Robotnik, an evil genius who wants to do experiments on him.
Some dialogue and subtitles options for Blu-ray not listed on container
Originally produced as a motion picture in 2020.
Based on the Sega video game.
"Technicolor."
Blu-ray extras: commentary by director Jeff Fowler and the voice of Sonic Ben Schwartz; Around the world in 80 seconds; deleted scenes; bloopers; "Speed me up" music video; For the love of Sonic; Building Robotnik with Jim Carrey; The blue blur: origins of Sonic; Sonic on set.
DVD contains feature film only. No extras.
Keywords: Sonic the Hedgehog -- (Fictitious character) -- Drama; Sheriffs -- Drama; Good and evil -- Drama; Heroes -- Drama; Supervillains -- Drama; Action and adventure films; Children's films; Comedy films; Feature films; Fiction films; Film adaptations; Juvenile works; Video recordings for people with visual disabilities